2015
DOI: 10.1177/0886260515591980
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Progression in Abused Women Following a Drug-Addiction Treatment Program

Abstract: This study explored the prevalence of victims of abuse and the therapeutic progression among women who sought treatment for drug addiction. A sample of 180 addicted Spanish women was assessed. Information was collected on the patients' lifetime history of abuse (psychological, physical, and/or sexual), socio-demographic factors, consumption variables, and psychological symptoms. Of the total sample, 74.4% ( n = 134) of the addicted women had been victims of abuse. Psychological abuse affected 66.1% ( n = 119) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Another 37 studies examined the association between psychological violence and depression; twenty-nine of the identified studies found a significant association [ 13 , 34 , 35 , 39 , 42 , 45 – 47 , 49 , 53 73 ], while five studies found a non-significant association [ 50 , 74 – 77 ]. Three studies did not report test-statistics [ 46 , 78 , 79 ]. For Hazen et al [ 61 ] and Lawrence et al [ 13 ] significant findings varied across subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Another 37 studies examined the association between psychological violence and depression; twenty-nine of the identified studies found a significant association [ 13 , 34 , 35 , 39 , 42 , 45 – 47 , 49 , 53 73 ], while five studies found a non-significant association [ 50 , 74 – 77 ]. Three studies did not report test-statistics [ 46 , 78 , 79 ]. For Hazen et al [ 61 ] and Lawrence et al [ 13 ] significant findings varied across subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…One surprising and worrisome piece of data obtained in this study is the high rate of mothers in the sample who had been victims of physical and/or sexual abuse (77.5 per cent). Although recent studies about the relationship between lifetime abuse and addictions have shown high rates of physical and sexual abuse among women seeking treatment for addictions problems (Fernández-Montalvo et al , 2015; Fernández-Montalvo, López-Goñi, Arteaga, Cacho and Azanza, 2017), no previous studies with mothers have been carried out. Nonetheless, the rate of abuse found in these patients was higher than expected, and it constituted the main variable related to mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of abuse is higher among patients in substance use disorder treatment (SUD-T) than in the general population (Jakubczyk et al, 2014;Olaya et al, 2015). The rates of physical abuse in patients with substance use disorder range from 18.0% to 53.7% (Fernández-Montalvo et al, 2015;Grundmann et al, 2018) and, in the case of sexual abuse, from 9.2% to 31.7% (Fernández-Montalvo et al, 2015;Fernández-Montalvo et al, 2017). Compared to patients without a history of abuse, patients who have experienced these traumatic events present a worse psychopathological profile and higher rates of treatment dropout (Brems et al, 2004;Daigre et al, 2015;López-Goñi et al, 2018).…”
Section: Impact Of a Trauma Intervention On Reducing Dropout From Substance Use Disorder Treatmentmentioning
confidence: 99%